Study of ozone disinfection in the hospital environment. Issue 4 (26th August 2020) - Tu, Le Hoang; Oanh, Le Hoang; Trung, Nguyen Vu; Cuong, Le Cao; Oanh, Doan Thi Yen; Dieu, Tran Vinh; Nghi, Nguyen Hoang
Abstract: Hundreds of millions of patients are affected by health care‐associated infections worldwide each year. In the hospitals, contaminated surfaces and air may play an important role in the transmission of respiratory pathogens. Recently, ozone disinfection is employed and shows the effectiveness as an alternative sanitizing technology to conventional disinfectants in reducing the microbial contamination in air as well as in the surfaces of the functional rooms of the hospitals. In this paper, the disinfection capacity of ozone gas is investigated by means of analysing the CFU reduction during ozonation of an operative theatre in Ha Dong polyclinic hospital (Hanoi, Vietnam). The full removal of the microorganisms and fungi in the operative theatre during ozonation was achieved by using ozone of 5 ppm concentration and exposure time of 40‐60 min.